Analysis of Seismic Activity near Theodore Roosevelt Dam, Arizona, during the Occupation of the EarthScope/USArray Transportable Array - Lockridge, Jeffrey (2012)
Rate and distribution of seismic activity are important indicators of the overall state of tectonic stress within a region. In regions characterized by low levels of seismicity, active fault surfaces are rarely visible at the surface, and the analysis of small-magnitude earthquakes at depth may be the most effective way to identify seismic hazard and risk from ambient tectonic activity. Further, studies of local and regional seismicity are also a direct way to examine geophysical and tectonic boundaries, although determining long-term seismicity levels requires good knowledge of the earthquake cycle. A major challenge in monitoring regions with low seismicity levels, therefore, is that long-term recording and/or deployment of sensitive instrumentation is required to provide adequate data. Seismicity patterns are of particular concern near large population centers and key infrastructure, such as power plants and dams. For instance, the Phoenix metropolitan area in southcentral Arizona receives its water through a network of canals fed by multiple man-made reservoirs located throughout the state. Analysis of seismicity patterns in the vicinity of these reservoirs and their associated dam structures is important because (1) the occurrence of an unexpectedly large earthquake may result in the failure of the dam structure resulting in adverse consequences to nearby human populations and the environment, and (2) the reservoir itself may induce seismicity and increase earthquake activity above previously recorded background levels (Simpson et al., 1986; Talwani, 1997; Gupta, 2002).